Influence of progressive upper limb strength training on table tennis athletes - Zhang, J. (Revista Brasileira de Medicina do Esporte, 2022)
Introduction: Progressive strength training can help athletes improve their strength levels quickly and safely. By controlling the frequency and amplitude of vibrations, muscles can produce unconscious and voluntary contractions that help prevent diseases such as osteoporosis.